2018
DOI: 10.1007/978-981-13-1286-1_5
|View full text |Cite|
|
Sign up to set email alerts
|

Central Circadian Clock Regulates Energy Metabolism

Abstract: Our body not only responds to environmental changes but also anticipates them. The light and dark cycle with the period of about 24 hours is a recurring environmental change that determines the diurnal variation in food availability and safety from predators in nature. As a result, the circadian clock is evolved in most animals to align locomotor behaviors and energy metabolism with the light cue. The central circadian clock in mammals is located at the suprachiasmatic nucleus (SCN) of the hypothalamus in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 192 publications
2
12
0
Order By: Relevance
“…Energy imbalance is associated with the development of obesity and NAFLD. It has been reported that food intake is suppressed in animals exposed to constant light 33 . In ND‐fed rats, the present study also showed a decrease in energy intake subjected to continuous light.…”
Section: Discussionsupporting
confidence: 75%
“…Energy imbalance is associated with the development of obesity and NAFLD. It has been reported that food intake is suppressed in animals exposed to constant light 33 . In ND‐fed rats, the present study also showed a decrease in energy intake subjected to continuous light.…”
Section: Discussionsupporting
confidence: 75%
“…In a population of healthcare workers, the phase shift of the master clock after 3-4 consecutive nightshifts could be 71% accounted for by intensity of light exposure according to the individual's baseline phase response curve (81). The SCN clock in turn regulates system wide energy metabolism as well as activity and food seeking behavior in alignment with these light-entrained rhythms (82). This finding helps to explain why, independent of other lifestyle factors (e.g., sleep duration, physical activity, and smoking), light at night (LAN) has been correlated with the increased risk of developing obesity in humans (83) and has been shown to acutely induce glucose intolerance in rats (84).…”
Section: Light At Nightmentioning
confidence: 99%
“…90 Eating late can cause circadian disruption, resulting in production of free cortisol, changes in daily rhythms of body temperature, decreased resting energy expenditure, and decreased glucose tolerance. 91,92 Thus, timing of meals could have serious implications not only for weight management, but also for development of cardiovascular disease. A recent review confirmed that skipping breakfast increased the risk of overweight and obesity.…”
Section: Meal Timingmentioning
confidence: 99%